IMPROVING STUDENT'S READING COMPREHENSION IN HUMOUR STORIES THROUGH LEARNING STARS WITH A QUESTIONS METHOD" AT THE SECOND GRADE OF MTS ARAFAH BITUNG - Lamusu, Agus Salim (ELLITE ( Journal of Education, Linguistics, Literature and Language Teaching), 2024)
The aim of this research was to determine whether Learning Starts With A Question Method (LSQ) can improving Student’s Reading Comprehension in humor stories text at MTs Arafah Bitung. This research is action classroom research, carried out at MTs Arafah Bitung Class VIIIA. Measures used in this study are as follows: (1) action planning, (2) Implementation of the action, (3) Observation, (4) Reflection. The action sequences is called a cycle of activity. Activity in this study conducted in two cycles. Each cycle consisted of two meetings. The technique collecting the data gained through observation guidelines teacher activities, student' activities and oral test. Data were analyzed by means of: The number of aspects obtained divided by the total aspects of assessment and then multiplied by one hundred percent. Based on the result of research before implementation of the action the number of students by 20 students. the average score is 41,8 and after the action cycle I increase to 66,6 and average score on the cycle II increased to 79,8. The total of student who achieve a minimum standard of completeness is also increasing. Before action is taken only 1 student (5%) who achieve a minimimun of completeness, at cycle I become 8 Students (40%), at the cycle II increased become 17 Students (85%). Therefore, it can be concluded that the use of Humor Stories Text and throwing the Learning With A Questions (LSQ) can be one way or alternative way to teaching English. Especially to improve the students' reading comprehension.